Triple bottom line and environmental sustainability: evolution of global ESG research—a bibliometric analysis - Pallavi Mishra; Vijay Kumar Pandey (Environmental Sciences Europe)
Abstract The evolution of Environmental, Social, and Governance (ESG) research represents a critical development in corporate sustainability practices, particularly in relation to the Triple Bottom Line perspective and specific United Nations Sustainable Development Goals (SDGs). This study examines this evolution through a comprehensive bibliometric analysis, focusing specifically on SDGs 7 (Affordable and Clean Energy), 8 (Decent Work and Economic Growth), and 12 (Responsible Consumption and Production), which are central to understanding the intersection of environmental sustainability and corporate performance. Through systematic analysis of the Scopus database from 2015 to March 2025, we examined 14,435 peer-reviewed articles using VOSviewer and Biblioshiny software packages. Following Callon’s density-centrality methodology, our analysis reveals four distinct thematic categories: motor themes (circular economy and sustainability assessment), basic themes (SDGs and corporate governance), Niche Themes (economic growth and emissions), and emerging themes (ESG integration). While developed economies (USA, UK, and EU) demonstrate the highest publication volumes, significant growth is observed in emerging regions, particularly in Southeast Asia, Latin America, and Africa, with distinct regional research priorities emerging post-2020. Publication patterns show exponential growth, peaking in 2023–2024, with notable acceleration in circular economy initiatives, alternative energy solutions, and green economy developments. Our findings highlight the growing integration of environmental performance metrics with financial outcomes and identify critical research gaps in ESG standardization, emerging market implementation, and technological innovation. The study projects continued growth in digital transformation, post-COVID resilience strategies, and sustainable business model innovation while acknowledging limitations in database coverage and language restrictions. These insights provide a comprehensive roadmap for future research directions in ESG implementation and sustainable business practices.